Peningkatan Hasil Belajar Peserta Didik Melalui Metode Tutor Sebaya Pada Pokok Bahasan Penyetaraan Reaksi Redoks - Ispi Yunita (Lembaga Bale Literasi, 2022)
This study aims to determine efforts to improve chemistry learning outcomes through the peer tutoring method for students in class XII IPA SMAN 1 Sukamulia for the 2021/2022 academic year. This research is a class action research. The subjects of this study were 23 students of class XII IPA. The object of this study is the peer tutoring method. The research step uses cycles for each activity consisting of planning, observing, implementing, and reflecting. The instruments used were tests and observations while data analysis used descriptive qualitative analysis. The results of the study can be concluded that the use of the peer tutoring method can improve student learning outcomes, as evidenced by the average score obtained in cycle I of 72.8 with classical completeness of 65%. In cycle II the average score was 76.7 with a classical completeness of 86.9%.